2021
DOI: 10.1159/000519701
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing Gene Panels and “Solo” Clinical Exome Sequencing Applied in Structurally Abnormal Fetuses

Abstract: <b><i>Objective:</i></b> The aim of the study was to assess the diagnostic yield of 2 different next-generation sequencing (NGS) approaches: gene panel and “solo” clinical exome sequencing (solo-CES), in fetuses with structural anomalies and normal chromosomal microarray analysis (CMA), in the absence of a known familial mutation. <b><i>Methodology:</i></b> Gene panels encompassing from 2 to 140 genes, were applied mainly in persistent nuchal fold/fetal hydrops a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In relation to the diagnostic yield of individual anatomical systems involved in cases with multisystem anomalies, the highest yields were observed for craniofacial dysmorphism (47% of fetuses with this anomaly were positive on ES), central nervous system anomalies (45%) and musculoskeletal anomalies (43%), while the lowest yields were for fetal hydrops (19%) and gastrointestinal anomalies (27%) (Figure 4 and Table S1). Among the 17 selected studies, only three reported data on incidental findings 22,31,32 , resulting in a frequency ranging from 1.1% to 6.1%, while four reported on secondary findings 4,26,27,29 , with a frequency ranging from 3.9% to 21%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In relation to the diagnostic yield of individual anatomical systems involved in cases with multisystem anomalies, the highest yields were observed for craniofacial dysmorphism (47% of fetuses with this anomaly were positive on ES), central nervous system anomalies (45%) and musculoskeletal anomalies (43%), while the lowest yields were for fetal hydrops (19%) and gastrointestinal anomalies (27%) (Figure 4 and Table S1). Among the 17 selected studies, only three reported data on incidental findings 22,31,32 , resulting in a frequency ranging from 1.1% to 6.1%, while four reported on secondary findings 4,26,27,29 , with a frequency ranging from 3.9% to 21%.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 121 abstracts found at that search, 24 articles were reviewed fully, of which 16 were deemed eligible for inclusion in the study 4,5,[18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Finally, our own series 32 was added. Among the 17 studies included in this systematic review, there were seven in which whole ES was performed, eight series in which only the OMIM genes were studied and two series in which the interpretation approach was not specified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA quality was determined by optical density using a DeNovix DS-11 instrument (Wilmington, DE, USA). The human exome was enriched using the KAPA HyperExome assay (Roche NimbleGen, Pleasanton, CA, USA) and massively sequenced using NovaSeq 6000 equipment (Illumina, San Diego, CA, USA), as described previously 12 . The average coverage depth achieved along the target regions was 65-140 × .…”
Section: Exome Sequencing and Copy Number Variation Analysismentioning
confidence: 99%